PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SD DI KECAMATAN SAGULUNG - Nimrod Sitinjak; Jarnawi Afgani Dahlan; Sri Tatminingsih (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study is intended to analyze the effect of pedagogic competence and professional competence on the performance of elementary school teachers in Sagulung District. The research method uses a quantitative approach with a causal design. Sampling using purposive sampling as many as 223 respondents. Data collection techniques using questionnaires, interviews, and documentation. The analysis technique uses descriptive statistics, and inferential statistics with multiple linear regression. From the results of multiple regression analysis, it can be concluded that the variables of pedagogic competence, and professional competence, simultaneously and significantly affect the performance of elementary school teachers in Sagulung District. It is recommended for further researchers, other variables related to teacher performance can be selected, such as school facilities, education budgets, or online learning methods in order to obtain objective, accurate, and complete information on research results.